Comparison of Some Methods for Estimating the Survival Function and Failure Rate for the Exponentiated Expanded Power Function Distribution - Sajit Khdair , Maysam; Hazim Aboudi, Emad (Journal of Economics and Administrative Sciences, 2022)
We have presented the distribution of the exponentiated expanded power function (EEPF) with four parameters, where this distribution was created by the exponentiated expanded method created by the scientist Gupta to expand the exponential distribution by adding a new shape parameter to the cumulative function of the distribution, resulting in a new distribution, and this method is characterized by obtaining a distribution that belongs for the exponential family. We also obtained a function of survival rate and failure rate for this distribution, where some mathematical properties were derived, then we used the method of maximum likelihood (ML) and method least squares developed  (LSD) to estimate the parameters and because of the nonlinear relationship between the parameters, numerical algorithms were used to find the estimates of the two methods. They are Newton-Raphson (NR) and Nelder mead (NM) algorithms to improve the estimators, and a Monte Carlo simulation experiment was conducted to evaluate the performance of the two algorithms' estimates, and the average integrated error criterion (IMSE) was used to compare the survival function estimates and the failure rate. The results showed the efficiency of the maximum likelihood method estimates and least squares developed using the two algorithms (NR, NM) where their results were close, and this shows the new distribution efficiency (EEPF) for modeling survival data.